Pengaruh Penggunaan Model Pembelajaran Concept Mapping Terhadap Hasil Belajar Siswa Sekolah Dasar - Mila Karmila; Lukman Lukman; Wahyu Anugrah Manippi (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
This research aims to determine the influence of the Concept Mapping model on the social studies learning outcomes of class V students at Inpres Batu Karaeng Elementary School, Bantaeng Regency. This research uses experimental and control classes. This investigation provides treatment in the form of concept outline procedures in VA lessons and regular learning in VB subjects. The method of collecting information in this research was carried out using procedures, tests and documentation. The research data were analyzed using graphic factual examination and inferential factual examination methods. From the investigation that occurred, it can be seen that in the control group 18 students completed independently, namely 4 students who met the minimum completion requirements (KKM) and 14 students who did not complete it, while for the experimental class there were 16 students who met the KKM 70 and 2 students who not totaled from 18 students. The results of the independent t-test obtained a value of 0.000, smaller than the stipulated value of 0.05, so it can be concluded that the concept map model has an effect on learning outcomes, even though the average learning broadcast has no impact on social studies learning outcomes.